IMPROVEMENT OF DIESEL MOTOR TECHNOLOGY LEARNING ACTIVITIES THROUGH COOPERATIVE LEARNING - EDI SETIYO (Sriwijaya University Learning and Education International Conference, 2016)
The objectives of this classroom action research, the model cycle. The object of thisresearch student’s courses diesel motor technology as much as 30 people. Datacollection using sheets of observation and tests. The results of this study showed amodel of cooperative learning can improve student learning outcomes and activitycourses for diesel, motor technology indicator asked with a percentage of 38,7%,70,4% answered the question, the motivation of students with a percentage of 91%and improves the results of the study with an average cycle I 64.5 cycle II became80.71. Based on the results of the research cooperative approach can be increasedthe results of the study.